Alternative Polysaccharide Wound Dressing from Heat-Moisture Starch/Basil Seed ( O. Basilicum L. ) Mucilage with Incorporated Glycolic Acid Antimicrobial Agent - Arnon Phonrat; Natkitta Subyai; Jutarat Prachayawarakorn (Journal of Macromolecular Science Part B, 2024)
In order to improve the behavior in water and the mechanical properties of heat-moisture treated starch, natural basil seed mucilage with high hydrophilicity and crystallinity was incorporated for wound dressing application. In addition, succinic acid cross-linking was used to enhance the durability of the material in water and glycolic acid was utilized as an antimicrobial agent. The effectiveness of the cross-linking process could be observed from the significant increase in dimensional stability from higher gel fraction value and increment of mechanical properties. Furthermore, the incorporation of glycolic acid into the wound dressing films demonstrated antibacterial efficacy, resulting in 100% bacterial reduction against S. aureus and E. coli strains. These films exhibited low cytotoxicity toward human epidermal keratinocytes (HaCaT) cells, indicating their potential for biomedical applications. Moreover, functional group analysis, crystallinity, morphology, thermal properties, gel fraction, water vapor transmission rate, free swell absorption, and mechanical properties were also examined.
Keywords: Food composition and properties; Polysaccharides Composition and Applications; Polysaccharides and Plant Cell Walls